Stanley Kubrick's The shining [videorecording (Blu-Ray)] - Kubrick, Stanley; Nicholson, Jack; Duvall, Shelley, 1949-; Lloyd, Danny, 1973-; Crothers, Scat Man; Nelson, Barry, 1920-2007; Stone, Philip, 1924-2003; King, Stephen, 1947- (Distributed by Warner Home Video, 2007)
Jack Torrance is a writer who, along with his family, comes to the elegant, isolated Overlook Hotel. He is the off-season caretaker. Torrance has never been there before, but maybe he has. The answer lies in a ghostly time warp of madness and murder.